2021
DOI: 10.1186/s12935-021-01958-0
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note to: miR-484 suppresses proliferation and epithelial–mesenchymal transition by targeting ZEB1 and SMAD2 in cervical cancer cells

Abstract: This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12935-021-01958-0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Zhou et al found that miR-200b-3p can target SMAD2 to promote the progression of melanoma ( Zhou et al,2020 ). Hu et al found that miR-484 inhibits the proliferation and epithelial-mesenchymal transition of cervical cancer cells by targeting ZEB1 and SMAD2 ( Hu et al,2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al found that miR-200b-3p can target SMAD2 to promote the progression of melanoma ( Zhou et al,2020 ). Hu et al found that miR-484 inhibits the proliferation and epithelial-mesenchymal transition of cervical cancer cells by targeting ZEB1 and SMAD2 ( Hu et al,2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[44] Herein, based on bioinformatic analyses, RNA pull-down, and luciferase reporter assays, we identi ed that circFOXK2 contained miR-484 response elements and could speci cally sponge to miR-484 that has been found to act as a tumor suppressor in various cancers, including cervical cancer and colorectal cancer. [45,46] In the pancreatic ductal adenocarcinoma (PDCA), Li et al reported that miR-484 suppresses PDCA growth via reducing Yes-associated protein (YAP) expression. [47] In HCC, we showed that Fis1 and its downstream mitochondrial ssion as a target of miR-484.…”
Section: Discussionmentioning
confidence: 99%
“…[44] Herein, based on bioinformatic analyses, RNA pull-down, and luciferase reporter assays, we identi ed that circFOXK2 contained miR-484 response elements and could speci cally sponge to miR-484 that has been found to act as a tumor suppressor in various cancers, including cervical cancer and colorectal cancer. [45,46] In the pancreatic ductal adenocarcinoma (PDCA), Li et al reported that miR-484 suppresses PDCA growth via reducing Yes-associated protein (YAP) expression. [47] In HCC, we showed that Fis1 and its downstream mitochondrial ssion as a target of miR-484.…”
Section: Discussionmentioning
confidence: 99%